CROSS-CULTURAL SYMBOLISM OF BLACK IN UZBEK AND END ENGLISH WORLDVIEWS (KONFERENSIYA, 2025)
This article explores the cross-cultural symbolism of the color black in Uzbek and English worldviews. Although black frequently symbolizes negativity, grief, or mystery in both cultures, its connotations, emotional value, and linguistic representations differ. The study analyzes idioms, metaphors, folklore, and cultural practices to identify similarities and differences in the semantic associations of the color black. The findings highlight how cultural experience, historical memory, and sociolinguistic practices shape the symbolic meanings of colors